Dżuma w Italii. O zapomnianym traktacie Della peste Angela Antonia Frari - Karwacka-Pastor, Dorota (Scripta Neophilologica Posnaniensia, 2021)
Angelo Antonio Frari, a 19th century doctor and writer, devoted his life to studying the plague. In his treaty entitled Della peste published in Venice in 1840, he presented the history of the plague pandemic, describing its symptoms and ways of curing throughout centuries. His work is not only a medical, anthropological, and ethical treaty, but also an account of events seen by a witness, who, having recovered from the plague, became involved in fighting with this disease in Italy and abroad. The author of the treaty delves into pondering on human nature, morality, and choices, and he presents various attitudes in the light of the epidemic. This work is also a source of information on how 19th century healthcare used to work and contains tips on how to avoid catching the disease. The subject matter of the treaty is still up to date, since the last word of this disease has not been said yet and it continues to be a threat to the human race.